Attracting Talented Researchers to Ireland: A review of The European Marie Curie Programme - GIORDANI, SILVIA (IUA, 2007)
The purpose of this publication is to illustrate how researchers in academia and industry in Ireland have successfully secured funding from Europe in the Marie Curie Programme and to highlight the impact this has had in furthering their R&D ambitions.
PUBLISHED
Keywords: Marie Curie Programme; Research; Funding; Research support; European programmes